2020
DOI: 10.1155/2020/8828456
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of the Nitrogen and Sulfur Codoped Carbon Dots for Detection of Lead and Copper Ions in Aqueous Solution

Abstract: Herein, by using the green and cheap L-cysteine as the precursor, nitrogen and sulfur codoped carbon dots (NS-CDs) were synthesized via a facile one-step hydrothermal method. The obtained NS-CDs showed the relatively narrow size distributions (2.1~3.9 nm) with the lattice spacing of 0.29 nm, as well as the excitation-dependent photoluminescence (PL) emission activity with the quantum yield (QY) of 18%. More interestingly, the PL intensity of NS-CDs was quenched by the addition of copper or lead ions (Cu2+ or P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The quenching process was related to the static quenching mechanism for the detection of Cu 2+ ions, which denotes that a non‐fluorescent ground‐state complex is formed by the interaction between S/N‐CDs and the quencher, i. e., Cu 2+ ions. This was supported from the analysis of the FTIR and XPS spectra, from where was confirmed that the Cu−O and Cu−S bonds were coordination styles for the Cu 2+ ions in the S/N‐CDs [74] …”
Section: Sensing Of Specific Ions Containing Metalsmentioning
confidence: 62%
See 1 more Smart Citation
“…The quenching process was related to the static quenching mechanism for the detection of Cu 2+ ions, which denotes that a non‐fluorescent ground‐state complex is formed by the interaction between S/N‐CDs and the quencher, i. e., Cu 2+ ions. This was supported from the analysis of the FTIR and XPS spectra, from where was confirmed that the Cu−O and Cu−S bonds were coordination styles for the Cu 2+ ions in the S/N‐CDs [74] …”
Section: Sensing Of Specific Ions Containing Metalsmentioning
confidence: 62%
“…This was supported from the analysis of the FTIR and XPS spectra, from where was confirmed that the CuÀ O and CuÀ S bonds were coordination styles for the Cu 2 + ions in the S/N-CDs. [74] In another recent investigation, Lan et al obtained CNPs, emitting in the range between 483 and 525 nm. The CNPs were obtained via a simple hydrothermal process using poly-3-thiopheneacetic acid (PTA) and NaOH.…”
Section: Copper Ions -Cu 2 +mentioning
confidence: 96%
“…The infrared spectrum of NSCDs is shown in Figure 2 b. Most of the observed peaks can be attributed to the different functional groups produced by the synthesis procedure; specifically, the peaks at 1112 cm −1 and 1401 cm −1 can be assigned to S = O bonds and C-S bonds, respectively, thus confirming the presence of sulfur [ 45 ]. In addition, the peak at 1523 cm −1 is due to C = N, while that at 752 cm −1 comes from N-H wagging [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum of pristine NS-CDs, some peaks are pointed out by arrows and attributed to the presence of different typical nitrogen functional groups produced by the hydrothermal synthesis of N-doped CDs [ 25 , 37 ]. Peaks at 1113 cm −1 and 1400 cm −1 may come from S=O bond and C-S bond, respectively, and indicate the presence of sulfur in NS-CDs [ 36 ]. Noticeable differences can be observed in the spectrum of NS-CDs + Cu(II) with all the peaks indicated by arrows strongly reduced due to interaction with Cu(II).…”
Section: Resultsmentioning
confidence: 99%
“…Within this framework, fluorescent sensing of Cu(II) ions has been the topic of many studies, both exploiting fluorescence quenching and turn-on effects [ 30 , 31 , 32 , 33 , 34 , 35 ]. Differently, absorption-based sensing of copper through CDs has rarely been reported [ 36 ] and deserves further investigations in view of applications to easy-to-use visual colorimetric devices.…”
Section: Introductionmentioning
confidence: 99%